2021
DOI: 10.32539/bsm.v5i4.409
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Intraoperative Ossicular Status and Conductive Hearing Loss Degree among Chronic Suppurative Otitis Media Patients in Dr Mohammad Hoesin General Hospital Palembang

Abstract: Background: Chronic suppurative otitis media (CSOM) is a chronic inflammation of the mucosa and periosteum of the middle ear and mastoid cavity that defined as a perforated tympanic membrane with persistent drainage for more than 2 months. Preoperative hearing threshold and air bone gap (ABG) assessment are expected to predict the ossicular status which can only be ascertained intraoperatively. This study aimed to determine the correlation between intra-operative ossicular status and the degree of conductive h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…They concluded that there is a substantial and robust association between ABG scores and ossicular status scores. The ossicular status score increases in proportion to the ABG, and vice versa [12].…”
Section: Discussionmentioning
confidence: 96%
“…They concluded that there is a substantial and robust association between ABG scores and ossicular status scores. The ossicular status score increases in proportion to the ABG, and vice versa [12].…”
Section: Discussionmentioning
confidence: 96%